Upaya Peningkatan Daya Dukung Tanah Dasar (Subgrade) dengan Menggunakan Campuran Fly Ash, Bottom Ash dan Silika - Putri, Silfa Nayyira; Putra, Andius Dasa; Iswan, Iswan; Syah, Aminudin (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2023)
Soil or subgrade is the place where the construction made by technicians for personal and collective interests stands. Before starting a construction, soils that have low bearing capacity, water absorption and high plasticity can be stabilised by soil stabilisation methods. Soil stabilization may involve the use of chemical stabilization materials. This research aims to determine the effect and get the appropriate comparison of the results of the addition of a mixture of fly ash, bottom ash and silica. This research study was conducted using soil samples from Kalianda subdistrict and stabilization materials in the form of fly ash, bottom ash and silica matured for 24 hours. Tests were conducted at the Soil Mechanics Laboratory and physical and mechanical properties were tested.. Clay soils classified as A-7-5 (AASHTO) and OH (USCS) mixed with 4 different compositions of stabilising materials had different results. Of the 4 compositions, the mixture that has the largest bearing capacity value is only silica. Because the results of the CBR test on the mixture that added silica were greater than the mixture using only fly ash and bottom ash. Fly ash, bottom ash and silica gel are easily found or affordable, but the use of silica can increase costs due to its relatively expensive price, inversely proportional to the very affordable price of fly ash and bottom ash.